Examining the Capacity of Indonesia’s Defense Entities on Countering Radicalism - Werijon, Werijon; Setiawan, Daniel (Advances in Social Sciences Research Journal, 2021)
Radicalism for the last few decades has hampered the people and national security building of Indonesia. Contemporary global and regional constellations develop an unprecedented scale of impact radicalism as well as its tractability. The formal categorization of radicalism as an ideology based-non-military threat reflects an imperative mandate for Indonesian defense entities to review and formulate relevant and comprehensive alleviation strategies to address the radicalism. However, this urgency does not appear to have been embodied in at least two points in our opinion: the perception among associated institutions barely aware of the significance of synergy and coordination and second, a minor portion of the countering of radicalism in the frame of the roadmap for Indonesia's national defense development. This research examines the perceptions of relevant defense stakeholders in Indonesia regarding radicalism and its current approach as well as the formulation of strategies that have been implemented or designed to maintain the existence of Indonesian nationalism. We collected information and data through both documentation studies and interviews with representative officials from the relevant ministries, military, and state agencies and then compiled it descriptively. By examining the perceptions of each research object as well as the construction of the strategy that has been rolled out, we conclude the Indonesian defense entities have yet significant, comprehensive, and sustainable strategies addressing the threat of radicalism.